DOP54 Efficacy and safety of ustekinumab through Week 16 in patients with moderate-to-severe ulcerative colitis randomised to ustekinumab: results from the UNIFI induction trial. (25th January 2019) - Danese, S; Sands, B E; O'Brien, C D; Zhang, H; Johanns, J; Sloan, S; Izanec, J; Szapary, P; Marano, C; Leong, R W; Rowbotham, D; Targan, S R; et al.
Abstract: Background: The objective was to evaluate the efficacy and safety of ustekinumab (UST) through Week 16 induction among patients with moderate–severe UC randomised to UST in the UNIFI Phase 3 clinical trial. Week 8 induction data have been previously reported. 1 Methods: Rates of overall clinical response and clinical remission among blinded patients randomised to IV UST induction were used to evaluate efficacy through Week 16. The number of patients who achieved each endpoint included patients who achieved the endpoint at Week 8 after initial IV UST induction and patients who achieved the same endpoint at Week 16 following a blinded dose of UST 90 mg SC at Week 8 if they were not in clinical response at Week 8. Results: Among patients randomised to UST at Week 0, 77.6% achieved clinical response within 16 weeks: 56.5% at Week 8 after IV induction and an additional 21.1% at Week 16 after receiving UST SC at Week 8. Among the Week 8 non-responders to UST IV induction who received UST SC at Week 8, 57.9% achieved clinical response at Week 16. Among patients randomised to UST at Week 0, 18.8% achieved clinical remission within 16 weeks: 15.6% at Week 8 after IV induction and an additional 3.2% at Week 16 after receiving an additional UST dose at Week 8. Among the Week 8 non-responders to UST IV induction who received UST SC at Week 8, 9.4% achieved clinical remission at Week 16. The proportions of patients who achieved clinical response within 16 weeks was lower for patients with a history of biological failure compared with non-biological failure patients: 70.6% vs. 84.9% (Table 1). Similarly, the proportions of patients who achieved clinical remission during induction within 16 weeks were lower for biological failure patients compared with non-biological failure patients: 13.3% vs. 24.7% (Table 2). The AE profile for patients who received a single UST IV dose and those with an additional UST dose SC at Week 8 were similar and consistent with the AE profile for patients that received PBO. Conclusions: UST is safe and effective induction therapy in patients with moderate–severe UC. Similar to results from the Crohn's disease programme, these data support a clinical rationale for continuing treatment with UST through at least one SC dose 8 weeks after IV induction in patients with moderate–severe UC. Reference 1. Sands BE, Sandborn WJ, Panaccione R et al . Safety and efficacy of ustekinumab induction therapy in patients with moderate to severe ulcerative colitis: results from the phase 3 UNIFI study. Oral Presentation at ACG 2018, 9 October 2018, Philadelphia, PA.